2020
DOI: 10.3389/fmicb.2020.538476
|View full text |Cite
|
Sign up to set email alerts
|

Aeolian Prokaryotic Communities of the Global Dust Belt Over the Red Sea

Abstract: Aeolian prokaryotic communities (APC) are important components of bioaerosols that are transported freely or attached to dust particles suspended in the atmosphere. Terrestrial and marine ecosystems are known to release and receive significant prokaryote loads into and from the surrounded atmospheric air. However, compared to terrestrial systems, there is a lack of microbial characterization of atmospheric dust over marine systems, such as the Red Sea, which receives significant terrestrial dust loads and is c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 54 publications
0
4
1
Order By: Relevance
“…Bacteroidetes, Firmicutes, and Actinobacteria abundances were more variable throughout the year and did not show a clear trend. Other frequent phyla previously described in air samples, such as Acidobacteria, Cyanobacteria, Chloroflexi, or Deinococcus-Thermus (Kellogg et al, 2004;Gao et al, 2017;Aalismail et al, 2020), were identified in less than 1% of the sequences in this study. Generally, summer samples showed the highest abundance levels at both sampling sites, similar to trends observed in previous reports (Bowers et al, 2012;Bertolini et al, 2013;Genitsaris et al, 2017;Núñez et al, 2021), but the highest number of unique OTUs for a given season corresponded to winter in this study.…”
Section: Seasonal Variationscontrasting
confidence: 54%
See 1 more Smart Citation
“…Bacteroidetes, Firmicutes, and Actinobacteria abundances were more variable throughout the year and did not show a clear trend. Other frequent phyla previously described in air samples, such as Acidobacteria, Cyanobacteria, Chloroflexi, or Deinococcus-Thermus (Kellogg et al, 2004;Gao et al, 2017;Aalismail et al, 2020), were identified in less than 1% of the sequences in this study. Generally, summer samples showed the highest abundance levels at both sampling sites, similar to trends observed in previous reports (Bowers et al, 2012;Bertolini et al, 2013;Genitsaris et al, 2017;Núñez et al, 2021), but the highest number of unique OTUs for a given season corresponded to winter in this study.…”
Section: Seasonal Variationscontrasting
confidence: 54%
“…Most of the relevant literature has reported similar findings. Proteobacteria is regularly the most frequent phylum in airborne samples ( Cáliz et al, 2018 ; Aalismail et al, 2020 ). However, percentages obtained here are significantly higher (>65%) than those of most previous studies (25–51%) ( Tringe et al, 2008 ; Barberan et al, 2014 ; Prussin et al, 2016 ; Abd Aziz et al, 2018 ; Tanaka et al, 2019 ; Uetake et al, 2019 ).…”
Section: Discussionmentioning
confidence: 99%
“…So, the dusts play key roles in nutrients enrichments that may support biological productivity. Meantime, the global dust belt bears heavy loads of microbes, virus, and bacteria cells that discharge over the LME # 33 (Aalismail et al, 2020) especially over the southern region and during summer season (Osipov & Stenchikov, 2018).…”
Section: Climate Changementioning
confidence: 99%
“…1, S4). This might be due to the Mediterranean bacteria's capacity to rapidly respond to dust input (Tsiola et al, 2017, Dinasquet et al, 2022, especially in the SSML (Astrahan et al, 2016) or to the direct deposition of dust attached bacteria (Rahav et al, 2016, Mescioglu et al, 2019, Aalismail et al, 2020 to the SSML.…”
Section: Spatial Distribution Of Bacteria Community Composition In Th...mentioning
confidence: 99%